Strategi promosi perpustakaan desa dalam merawat eksistensi di masa kini - Sawiti, Ahmad; Fathullah, Amal (S1 Ilmu Perpustakaan dan Informasi Islam FTK UIN Antasari Banjarmasin, 2023)
This research aims to uncover the promotional strategies used by the Berkat Ilmu Village Library in Tambak Sirang Laut Village, Banjar Regency, South Kalimantan Province, to remain relevant in the era of digitization. This study is a qualitative field research with the object of research being the promotional strategies of the Berkat Ilmu Village Library in Tambak Sirang Laut Village. The subjects of the study are the Head of the Berkat Ilmu Village Library and two library staff members. Data collection techniques include interviews, observations, and documentation. Data analysis involves three stages: data reduction, data presentation, and drawing conclusions. The research findings reveal that the promotion of the Berkat Ilmu Village Library in Tambak Sirang Laut Village includes creating the name